Management of compromised residual alveolar ridges using hollow denture with three-dimensional printed spacer and specialized impression technique - Navdeep Singh; Parag Dua; N Thiruvalluvan; Saurav Kumar; Sonam Yangchen (Wolters Kluwer Medknow Publications, 2023)
Impression making in compromised residual alveolar ridge is a regular challenge in rehabilitating patients with conventional removable complete dentures. In patients who cannot afford implant-supported dentures, specialized impression technique is a viable and justified option for fabrication of complete dentures. More often, the stability of denture in such patients becomes a deciding factor between failure and success. Furthermore, increased interarch space may result in increased height of maxillary and/or mandibular dentures with corresponding increase in weight, which further compromises the retention and stability of the prosthesis. This article describes an amalgamation of Hobkirk's impression technique in a case of resorbed maxillary residual alveolar ridge with a flabby anterior segment and fabrication of hollow maxillary dentures using a "three-dimensional printed dental spacer" with a "double-flask technique." The weight of the final prosthesis was reduced therefore contributing to improved retention and stability of the final prosthesis.